Strategi Politik: Preferensi Partai Politik Menghadapi Pemilu di Aras Lokal - M. Tinov; Tito Handoko (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This paper aims to outline the political situation and the political strategy of political parties in the face of political contestation in the realm of local politics. This article objectively the underlying thoughts on some of the problems faced by political parties, namely; First, that the majority of political parties have not been able to build a party structure to the deepest levels lower in real terms, and the Second, political parties tend to show the face of the management of the party that the conventional / traditional, less utilize information technology systems and the lack of measuring instruments used by political parties in facing political contest, especially in the realm of local politics. Moreover, political parties also have not been able to demonstrate clearly the number of cadres, Party members and sympathizers at various levels of the party structure. This paper on the theory of thought underlying political strategy Peter Schroder. In the data-collection efforts, this paper emphasizes the qualitative data acquisition with a literature study. The study concludes that the political strategy that can be done by political parties in the face of political contest local include strategic political mapping, preparation of planning, building resources, analysis of internal and external environment, strategize major influence voting behavior, mobilization, imaging and coordination.